Relationship Between Motivation And Job Satisfaction Among Non-Academic Employees Of A Private University - Pahlavanzadeh, Solmaz (2011)
The aim of this research is to investigate the relationship between motivation (intrinsic and extrinsic) and job satisfaction among employees. A correlational cross-sectional research design was used for this study and the survey method was used to collect data.